Enhancing Tax Compliance in MSME Tax Reporting: The Role of Tax Awareness, Trust, and Socialization - Widjaja, William; Ariana, Yovita; Michael, Michael (E-Jurnal Akuntansi, 2024)
A crucial component of growth, tax compliance is impacted by a number of variables including awareness, trust, and socialization. In light of this, the purpose of this study is to examine how these variables affect MSMEs' tax compliance. MSMEs in Tanah Abang, Jakarta, one of Indonesia's economic hubs where MSMEs predominate, make up the research population. Through the use of surveys and quantitative analysis, a sample size of 100 MSMEs respondents was employed. SEM-PLS software was used to perform data analysis techniques. The study's findings demonstrate a strong positive correlation between tax awareness and compliance trust. Tax socialization, however, has no significant effect on compliance and neither does it moderate the effect of trust on compliance. Keywords: Tax Compliance; Tax Awareness; Taxpayer Trust; Tax Socialization; Tax Regulation